2015
DOI: 10.4049/jimmunol.1501223
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1 but Not Caspase-11 Is Required for NLRC4-Mediated Pyroptosis and Restriction of Infection by Flagellated Legionella Species in Mouse Macrophages and In Vivo

Abstract: Gram-negative bacteria from the Legionella genus are intracellular pathogens that cause a severe form of pneumonia called Legionnaires’ disease. The bacteria replicate intracellularly in macrophages, and the restriction of bacterial replication by these cells is critical for host resistance. The activation of the NAIP5/NLRC4 inflammasome, which is readily triggered in response to bacterial flagellin, is essential for the restriction of bacterial replication in murine macrophages. Once activated, this inflammas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 47 publications
1
69
0
10
Order By: Relevance
“…This result was quite unexpected in that all the experiments performed in vivo and in vitro with strain R99, including those performed in the present work, have never suggested the existence of an intracellular stage in the life cycle of this pathogen in any of its hosts. The unexpected up-regulated genes were for: (i) recognition of intracellular pathogens, such as, TLR9 and NOD2 ; (ii) chemo-attraction of macrophages, natural killer cells, and lymphocytes such as, CCL4 (MIP-1β; Macrophage inflammatory protein-1β), a gene that was highly activated at all sampling points, and that was also early up-regulated in gills from infected eels (Callol et al, 2015a); (iii) regulatory CK such as, LTA (or TNF-β), IL-17 (implicated in triggering and mediating pro-inflammatory response, by inducing the expression of different pro-inflammatory CKs, CCs, antimicrobial peptides, growth factors among others); iv) IFN-related genes (associated with CD8 + T cells) such as, ifna2, Ifnb1, Ifnar1 , and Ifngr1; (v) CKs involved in the regulation and stimulation of haematopoiesis such as, IL-3, IL-4, IL-7 and CSF2 (this activation could lead to a rapid innate immune system replenishment, exacerbating the inflammatory response); (vi) the inducible NO synthase gene that mediates tumoricidal and bactericidal actions, mainly intracellular (Maeda and Akaike, 1998); and (vii) members of the inflammasome complex such as, NLRC4, PYCARD, and Caspase-1, that have been previously involved in macrophage death by pyroptosis induced by the facultative intracellular pathogen Legionella pneumophila (Case and Roy, 2011; Cerqueira et al, 2015). We also found evidence of a dysregulation of CK production.…”
Section: Discussionmentioning
confidence: 99%
“…This result was quite unexpected in that all the experiments performed in vivo and in vitro with strain R99, including those performed in the present work, have never suggested the existence of an intracellular stage in the life cycle of this pathogen in any of its hosts. The unexpected up-regulated genes were for: (i) recognition of intracellular pathogens, such as, TLR9 and NOD2 ; (ii) chemo-attraction of macrophages, natural killer cells, and lymphocytes such as, CCL4 (MIP-1β; Macrophage inflammatory protein-1β), a gene that was highly activated at all sampling points, and that was also early up-regulated in gills from infected eels (Callol et al, 2015a); (iii) regulatory CK such as, LTA (or TNF-β), IL-17 (implicated in triggering and mediating pro-inflammatory response, by inducing the expression of different pro-inflammatory CKs, CCs, antimicrobial peptides, growth factors among others); iv) IFN-related genes (associated with CD8 + T cells) such as, ifna2, Ifnb1, Ifnar1 , and Ifngr1; (v) CKs involved in the regulation and stimulation of haematopoiesis such as, IL-3, IL-4, IL-7 and CSF2 (this activation could lead to a rapid innate immune system replenishment, exacerbating the inflammatory response); (vi) the inducible NO synthase gene that mediates tumoricidal and bactericidal actions, mainly intracellular (Maeda and Akaike, 1998); and (vii) members of the inflammasome complex such as, NLRC4, PYCARD, and Caspase-1, that have been previously involved in macrophage death by pyroptosis induced by the facultative intracellular pathogen Legionella pneumophila (Case and Roy, 2011; Cerqueira et al, 2015). We also found evidence of a dysregulation of CK production.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of cytosolic PRRs trigger inflammasome-dependent activation of caspase-1 and caspase-11, resulting in pyroptotic cell death and release of IL-1 family cytokines, including IL-1␣ and IL-1␤. Infection with T4SS-expressing L. pneumophila activates multiple inflammasomes, including a flagellin-dependent NAIP5 inflammasome, an NLRP3 inflammasome that responds to an unidentified T4SS-dependent signal, and a noncanonical caspase-11 inflammasome that detects hexa-acylated or penta-acylated lipid A (20,71,72,(94)(95)(96)(97)(98)(99)(100)(101). Unlike L. pneumophila, C. burnetii does not produce flagellin and would not be expected to activate the NAIP5 inflammasome (102).…”
Section: To E) Tlr2mentioning
confidence: 99%
“…Caspase-11 activation in response to L. pneumophila is flagellin independent; accordingly, the caspase-11 pathway cooperates with the flagellin/NLRC4 pathway to induce caspase-1 cleavage and IL-1b production [64,85]. Experiments performed with caspase-11 2/2 mice in various mouse genetic backgrounds indicated that caspase-11 is not required for the suppression of L. pneumophila replication in macrophages and in vivo [91]. However, the role of caspase-11 in the suppression of L. pneumophila replication is still controversial.…”
Section: Caspase-11 and Noncanonical Activation Of The Nlrp3 Inflammamentioning
confidence: 99%